Diet Containing Soy Protein Concentrate with Low and High Isoflavones for 18 Weeks Protects Against Non-alcoholic Fatty Liver Diseases. (14th June 2022) - Hakkak, Reza; Spray, Beverly; Irby, David; Korourian, Soheila
Abstract: Objectives: To examine the role of isoflavones levels in soy protein diets on protection against NAFLD in an obese rat model. Methods: 42 six-week old lean (L, n = 21) and obese (O, n = 21) Zucker rats were randomly assigned to one of 3 dietary groups after one week of acclimation: casein diet (C = control), soy protein with low isoflavones (LIF), or soy protein with high isoflavones (HIF) for 18 weeks (n = 7 rats/group). Rats were weighed twice weekly. After 18 weeks, rats were sacrificed and livers were weighted and samples were taken for histopathological analysis. The steatosis was semiquantitated as a score of 0 to 4 in each case based on relative degree of steatosis within hepatocytes: (0) no steatosis; (1) <25%; (2) 25–50%; (3) >50–75% and (4) >75%. Serums were collected to measure alanine aminotransferase (ALT) and aspartate aminotransferase (AST) using VetScan VS@ profile. Results: Obese rats gained significantly more weight than lean rats for all three diet groups, with no significant difference between obese OLIF vs. OHIF groups. Obese rats (OC) had a significant (P < 0.0001) increased liver steatosis scores and liver weight compared to lean rats (LC). The OHIF and OLIF-fed rats significantly (P < 0.0001) lowered the steatosis scores and liver weight compared to OC (p < 0.0001). However, there were no significant differences between for steatosis score or liver weight for OLIF vs. OHIF. There were no significant differences in either AST or ALT levels between any combination of diet group. Conclusions: We found that soy protein concentrate protects against liver steatosis and protection is greater with a higher concentration of isoflavones. Funding Sources: This project is support USDA #12889791 to RH.